Evaluation of anti-urolithiatic effect of aqueous extract of Bryophyllum pinnatum (Lam.) leaves using ethylene glycol-induced renal calculi - Apexa Bhanuprasad Shukla; Divyesh Rasikbhai Mandavia; Manish Jasmatbhai Barvaliya; Seema Natvarlal Baxi; Chandrabhanu Rajkishore Tripathi (Mashhad University of Medical Sciences, 2014)
Objective: To investigate the anti-urolithiatic effect of aqueous extract of leaves of Bryophyllum pinnatum (B. pinnatum) on ethylene glycol-induced renal calculi. Materials and Methods: Thirty-six Wistar male rats were randomly divided into six equal groups. group A animals received distilled water for 28 days. Group B to group F animals received 1% v/v ethylene glycol in distilled water for 28 days and group B served as ethylene glycol control. Groups C and D (preventive groups) received aqueous extract of leaves of B. pinnatum 50 and 100 mg/kg intraperitoneally, respectively for 28 days. Groups E and F (treatment groups) received aqueous extract of leaves of B. pinnatum 50 and 100 mg/kg intraperitoneally, respectively from 15th to 28th day. On days 0 and 28, 24 hrs urine samples were collected for urinary volume and urinary oxalate measurement. On day 28, blood was collected for serum creatinine and blood urea level monitoring. All animals were sacrificed and kidneys were removed, weighed, and histopathologically evaluated for calcium oxalate crystals deposition. Results: Administration of aqueous extract of leaves of B. pinnatum reduced urine oxalate level significantly, as compared with Group B (p